The Attitudes to the Assistance to Developing Countries (Czech Journal of International Relations, 1967)
Current developments testify to the fact that the pace of economic growth is developingthe country is still insufficient to respond to urgent social issues and to bridge the gap that separates these countries from the economic level of the developed country. According to the goals announced in the UN Development Decade the RZ should reach a five percent rate of growth of the gross social product by the end of the 1960s. In fact however, in the years 1960-64, the average increase in gross product (GDP) dropped to 4% from the 4.5% achieved in the period 1955-60 and as a result fell in the same period gross product per capita to 1.5% from the previous 2.4%.